2019
DOI: 10.1093/mnras/stz1668
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the albedo and disc on the zero velocity curves and linear stability of equilibrium points in the generalized restricted three-body problem

Abstract: The most important aspects of a dynamical system are its stability and the factors which affects the stability property. This paper presents the analysis of the effects of albedo and disc on the zero velocity curves, existence of equilibrium points and on their linear stability in a generalized restricted three body problem that consists of motion of an infinitesimal mass under the uniform gravity field of radiating-oblate primary, oblate secondary and a disc, which is rotating about the common center of the m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 48 publications
0
29
0
Order By: Relevance
“…Two infinitesimal bodies, P 1 and P 2 , of dimensionless masses µ 1 and µ 2 , respectively, move in the gravitational field while mutually attracting each other without perturbing the primaries. The perturbed mean motion n can be considered as in [15][16][17][18],…”
Section: Formulation Of the Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Two infinitesimal bodies, P 1 and P 2 , of dimensionless masses µ 1 and µ 2 , respectively, move in the gravitational field while mutually attracting each other without perturbing the primaries. The perturbed mean motion n can be considered as in [15][16][17][18],…”
Section: Formulation Of the Modelmentioning
confidence: 99%
“…Dustbelt-like structures are also present in the Proxima Centauri system. Many researchers have studied the effect of the asteroid belt in CRTBP [13][14][15][16], and found that these perturbations exhibit significant changes in the equilibrium position. In this paper, we investigate some new aspects of R2+2BP, along with the disk-like belt effect on the potential function; as such, we found the change in the equilibrium positions.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming that the dominant bodies are in elliptical motion with constant angular velocity n(mean motion), then the orbits of m 1 and m 2 with respect to the centre of mass, with semi-major axes, would be a 1 � (m 2 /(m 1 + m 2 ))a and a 2 � (m 1 /(m 1 + m 2 ))a, respectively, having the same eccentricity; thus, the motion of the bigger and smaller primary can be written as [1,28]…”
Section: Equations Of Motionmentioning
confidence: 99%
“…Also, the orbital eccentricity of the Earth is e ∼ 0.0167. Now, the dynamical flattening parameters of the primary bodies are given by e radiation pressure factor of the Sun q is defined as q � 1 − α such that α can be expressed as α � (L ⊙ /(2πGm 1 cκ)) [28], where L ⊙ is the luminosity of the Sun, G is the gravitational constant, c is the speed of light, and κ is the mass per unit area. By using Stefan-Boltzmann's law, the luminosity of the primary can be expressed as…”
Section: Numerical Applicationmentioning
confidence: 99%
See 1 more Smart Citation